Everyday Oracle DBA - Wells, April J. (McGraw Hill, 2006)
Learn how to effectively and efficiently administer an Oracle database and handle a variety of daily tasks with ease. Filled with tips, tricks, and shortcuts, Everyday Oracle DBA is designed to make your job easier and more productive. The book covers database setup, user management, PL/SQL, backup, restoration, tuning, troubleshooting, testing, and much more. Get the answers you need right at your fingertips from this Oracle Press guide.